Case Report: MOGAD - a steroid-responsive autoimmune meningoencephalitis mimicking infection - Yihui Goh; Priscillia Lye; Paul Anantharajah Tambyah; Derek Soon; Nares Smitasin; Jonathan Ong; Yong Cai; Yee Cheun Chan; David Tang; Kay Wei Ping Ng; Raymond C.S. Seet; Amy M.L. Quek (2025)
This case series reports three patients initially managed for presumed infectious meningoencephalitis, who were ultimately diagnosed with myelin oligodendrocyte glycoprotein associated disease (MOGAD). Their clinical presentations were strikingly similar to those of acute infectious meningoencephalitis, which posed a challenge to the initial diagnostic process. Notably, despite the absence of typical radiological changes associated with MOGAD, such as cerebral cortical encephalitis, these patients exhibited focal neurological and electroencephalographic changes. This series highlights the importance of considering MOG antibody testing in cases of aseptic meningoencephalitis, where early and accurate diagnosis can influence treatment decisions and patient outcomes in this steroid-responsive condition.